Estimation of Lung Cancer Risk Due to Radon Exposure in Natural Food Spices - , C. P. Ononugbo; , G. O. Avwiri (Archives of Current Research International, 2018)
Estimation of lung cancer risk for internal exposure to naturally occurring 222Rn gas in natural food spices was done using mathematical models. A series of equations were used to estimate Rn concentrations indoor and outdoor and the associated annual effective doses and lung cancer risk in some specified population according to their smoking habit. Activity concentration of 222Rn in the natural food spices range from 0.57 Bqm-3 (in white onions) to 686.19 Bqm-3 (in Tomatoes). Green pepper also recorded high value of 583.34 Bqm-3 while 222Rn in air ranges from 0.0018 to 2.17 Bqm-3. 222Rn exposure (WLM) in indoor due to ingestion of the natural food spices ranged from 0.0000127 WLM/y in white onions to 0.0153 WLM/y in tomatoes. The exposure from outdoor air due to radon inhalation ranged from 0.00000063 WLM/y in white onions to 0.0000724 WLM/y in tomatoes. The maximum indoor and outdoor values were 137.32 and 651.0 µSv/y respectively, detected in tomatoes. The minimum indoor and outdoor values were 0.114 and 0.0.54 µSv/y respectively, detected in white onions. The mean annual effective dose from ingestion of 222Rn and inhalation from the food spices are 15.39 and 0.72 µSvy-1 respectively. As regards the estimation of lung cancer attributable to exposure to 222Rn and its progeny to the general public, current smokers, ever smoker and never smoker recorded the maximum indoor and outdoor lung cancer risks of 381, 1144, 738 and 127 per million population and 54, 162, 105 and 4 per thousand populations respectively. The minimum indoor and outdoor risks were 32, 95, 61 and 11 per million population and 4, 13, 8 and 1 per thousand populations respectively. The result revealed a significant lung cancer risk for the current smokers.